أهمية بنوك المصطلحات الآلية في الترجمة والتعريب The Importance Of Automated Terminology Banks In Translation And Arabization - زروقي, عبد القادر (جامعة الوادي - University of Eloued, 2021)
يتناول هذا البحث ماهية بنوك المصطلحات الآلية وميزاتها، وأشهرها في العالم العربي والغربي، وكذا تبيان الفرق بينها وبين المعاجم الإلكترونية، كما تعرّض البحث إلى مسألة تعدّد المصطلحات العلمية، هذه القضية التي أصبحت تمثّل مشكلًا أمام الباحثين والدارسين، والمترجمين بالخصوص، وبناء على هذا جاءت هذه الدراسة بطريقة نحاول من خلالها استغلال إمكانات بنوك المصطلحات في تعريب المصطلح وتوحيده، والسعي لإشاعته وتداوله بين المختصين، وكذا الاستفادة من هذه البنوك في ميدان التأليف والترجمة. In this study we will shed light onthe nature and advantages on some of the well-knownautomated terminology banks in the Arab and Western world, and we will also identify the difference between them and electronic dictionaries. This study is also an attempt to investigate the question of the multiplicity of scientific terms, which has become a problem for researchers, scholars and translators in particular. The purpose of this study is to attempt to exploit the potential of terminology banks in the arabization and standardization of terms, to seek to disseminate them and to increase the frequency of their usage among specialists, and to find ways on how to benefit from those banks in the field of translation and writing.
مقال
Keywords: بنوك مصطلحات، ترجمة، تعريب، توحيد مصطلحات، حوسبة; Terminology banks – Translation – Arabization – Standardization of terms –Computing